THE BIOSYNTHESIS OF ROSMARINIC ACID IN SUSPENSION CULTURES OF COLEUS BLUMEI
Suspension cultures of Coleus blumei accumulate very high amounts of rosmarinic acid, an ester of caffeic acid and 3,4-dihydroxyphenyllactate, in medium with elevated sucrose concentrations. Since the synthesis of this high level of rosmarinic acid occurs in only five days of the culture period, the activities of the enzymes involved in the biosynthesis are very high. Therefore all the enzymes necessary for the formation of rosmarinic acid from the precursors phenylalanine and tyrosine could he isolated from cell cultures of Coleus blumei: phenylalanine ammonia-lyase, cinnamic acid 4-hydroxylase, hydroxycinnamoyl:CoA ligase, tyrosine aminotransferase, hydroxyphenylpyruvate reductase, rosmarinic acid synthase and two microsomal 3- and 3`-hydroxylases. The main characteristics of these enzymes of the proposed biosynthetic pathway of rosmarinic acid will he describes.